PETERNAKAN KAMBING ETAWA DI KABUPATEN TANAH DATAR - Dwi Yuzaria (Lembaga Pengabdian pada Masyarakat, 2015)
Most of Community of Kenagarian Barulak, District Tanjung Baru, Tanah Datar livelihood is farming crops, horticulture and animal husbandry Etawa goat. Waste food crops such as rice, maize, cassava and sweet potatoes are materials forages for goats and waste goat manure can be organic fertilizer on their farms, thus increasing the efficiency of production costs both areas, but the potential is not used optimally in accordance with good farming practice model. One group of farmers in this area are farmers group Boncah Saiyo cooperation with SME Top Boncah in the marketing of milk. The main objective of this IbM activity was Income generating or increased revenues of Boncah group farmers through the introduction of knowledge as good breeding management, knowledge of fodder, knowledge of reproduction, post-harvest technology and marketing management. It is also necessary knowledge of the factors of the marketing mix such as a) the diversification of products into pasteurized milk, yoghurt, ice cream, soap and other products, so that products can be accepted by consumers in the broader market, b) the determination of the selling price which is affordable for consumers, c) the expansion of marketing network both locally and outside the region, even outside the province to increase sales volume, d) the introduction of ways of promotion to farmers in order to introduce processed products to the public by opening outlets in several strategic places of interest and print brochures. The results of IbM's activities for coaching, training and mentoring the breeders group effort to increase the population, milk production, post harvest and marketing their product including : 1) improve the entrepreneurship spirit of breeders as an effort to support the development of the group; 2) business group has the ability of business planning, 3) improve the ability of the breeders group in conducting business operations; 4) enhance cooperation networks business.